Friction and Wear Phenomena of Vegetable Oil–Based Lubricants with Additives at Severe Sliding Wear Conditions. Issue 2 (4th March 2018) - Bahari, Adli; Lewis, Roger; Slatter, Tom
ABSTRACT: The tribological responses of palm oil and soybean oil, combined with two commercial antiwear additives (zinc dialkyl dithiophosphate and boron compound), were investigated at a lubricant temperature of 100°C and under severe contact conditions in a reciprocating sliding contact. The friction coefficient of palm oil with zinc dialkyl dithiophosphate was closest to the commercial mineral engine oil, with a 2% difference. The soybean oil with zinc dialkyl dithiophosphate produced a 57% improvement in wear resistance compared to its pure oil state. The existence of boron nitride in vegetable oils was only responsive in reduction of wear rather than friction. The response of commercial antiwear additives with vegetable oils showed a potential for the future improvement in the performance of vegetable oils.